Surgical Treatment for Occipital Condyle Fracture, C1 Dislocation, and Cerebellar Contusion with Hemorrhage after Blunt Head Trauma - Shigeo Ueda; Nobuhiro Sasaki; Miyuki Fukuda; Minoru Hoshimaru (Case Reports in Orthopedics)
Occipital condyle fractures (OCFs) have been treated as rare traumatic injuries, but the number of reported OCFs has gradually increased because of the popularization of computed tomography (CT) and magnetic resonance imaging (MRI). The patient in this report presented with OCFs and C1 dislocation, along with traumatic cerebellar hemorrhage, which led to craniovertebral junction instability. This case was also an extremely rare clinical condition in which the patient presented with traumatic lower cranial nerve palsy secondary to OCFs. When the patient was transferred to our hospital, the occipital bone remained defective extensively due to surgical treatment of cerebellar hemorrhage. For this reason, concurrent cranioplasty was performed with resin in order to fix the occipital bone plate strongly. The resin-made occipital bone was used to secure a titanium plate and screws enabled us to perform posterior fusion of the craniovertebral junction. Although the patient wore a halo vest for 3 months after surgery, lower cranial nerve symptoms, including not only neck pain but also paralysis of the throat and larynx, improved postoperatively. No complications were detected during outpatient follow-up, which continued for 5 years postoperatively.